Differential Protection Scheme for A Micro Grid with Inverter-Type Sources Based On Positive Sequence Fault Currents - Alhadrawi, Zaid; Abdullah, M. N.; Mokhlis, Hazlie (International Journal of Integrated Engineering, 2022)
There is a large difference in fault current level between the GC and IS mode for a microgrid (MG) with inverter-based distributed generators (IBDGs). The fault currents are minimal in the IS mode owing to the low current-carrying capacity of power electronics devices. Therefore, the coordination of traditional overcurrent (OC) protection is difficult for these two operation modes. Therefore, a comprehensive MG protection scheme should be established to safeguard MG against all kinds of faults. This paper proposes a positive sequence differential current protection scheme as the main protection. The envisioned concept can overcome the protective device coordination problems, and all fault types can be detected during both operation modes of MG, grid-connected (GC), and islanded (IS) for radial and loop configuration. The validation of the proposed design is performed using PSCAD/EMTDC software. The results show that the maximum fault clearing time for the main protection in GC mode and IS mode of 31.5 ms and 34 ms respectively. Compared with other schemes, the proposed scheme has a faster clearing time and is less expensive.